Modification of wine phenolic profiles by gibberellic acid application in 'Cabernet Gernischt' grapevines before anthesis. (26th September 2022) - Song, Jianqiang; Zhang, Ang; Gao, Fei; Liang, Haizhong; Li, Mingqing; Zhang, Jie; Wang, Genjie; Qu, Huige; Cheng, Shiwei; Ruan, Shili; Li, Jiming
Abstract: BACKGROUND: Vitis vinifera L. 'Cabernet Gernischt' grapes from the Yantai wine region of China usually form dense clusters and contain low phenolic content. We applied five concentrations (ranged from 5 to 25 mg L −1 ) of gibberellic acid (GA3 ) to 'Cabernet Gernischt' before anthesis to decrease cluster compactness in two consecutive vintages. Yield indices, grape maturity, and wine phenolic compounds were determined. RESULTS: GA3 application significantly reduced cluster compactness, bunch weight, and yield per vine, but it did not significantly improve fruit ripening. The levels of total phenolics, total tannins, and total anthocyanins in wine were enhanced by GA3 application, with 10 and 15 mg L −1 GA3 treatments consistently producing a significant increase in the concentrations of mavidin, cyanidin, and their derivatives. Specifically, trans ‐resveratrol was consistently significantly increased by 15 mg L −1 GA3 application. Principal component analysis of phenolic compounds demonstrated the differences among wines produced from GA3 treatment groups and the control. CONCLUSION: Overall, wine phenolic profiles could be significantly modified by application of low concentrations of GA3 before anthesis. Application of high levels of GA3 is not recommended due to significant yield decrease. © 2022 Society of Chemical Industry.